Tribological behaviour of C/C–SiC composites—A review - Kumar, Parshant; Srivastava, V. K. (Tsinghua University Press, 2016)
Ceramic matrix composites made of carbon fibres and carbon matrix (C/C) are generally used for aircraft structures and brake discs due to their low density, and good thermal, mechanical, and tribological properties. Silicon carbide (SiC) can be introduced to the matrix to improve the performance of C/C composites, because it increases the hardness and thermal stability, and decreases the chemical reactivity, which leads to the improvement of tribological properties of C/C composites. Thus carbon–carbon silicon carbide (C/C–SiC) composites can be used at high temperature for the application of brake discs, friction clutches, etc. C/C–SiC composites are fabricated by three different methods: (i) chemical vapour infiltration (CVI), (ii) polymer infiltration and pyrolysis (PIP), and (iii) liquid silicon infiltration (LSI), among which LSI method is widely used for the fabrication of C/C–SiC composites due to higher mechanical and thermal properties.
Keywords: carbon–carbon (C/C) composites; coefficient of friction; wear